2023
DOI: 10.1007/s00259-023-06119-1
|View full text |Cite
|
Sign up to set email alerts
|

Extended therapy with [177Lu]Lu-PSMA-617 in responding patients with high-volume metastatic castration-resistant prostate cancer

Abstract: Purpose The currently used scheme for radioligand therapy (RLT) of patients with metastatic castration-resistant prostate cancer (mCRPC) consists of 4–6 cycles of 6.0–7.4 GBq [177Lu]Lu-PSMA-617 each. This standard treatment scheme has proved safe and effective resulting in objective response in most patients with no significant toxicity. Many patients, however, show high-volume residual tumor burden after the sixth cycle and may benefit from treatment continuation. Extended treatment with additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Most patients presented extra decline in PSA (81%) and positive image-based response with 11/21 (52.3% presenting partial response [PR] or stable disease [SD]) with acceptable grade ≥3 toxicity in 15% of patients. 38 Gaudreault et al 39 evaluated 6 patients that were excluded from the LuPSMA trial with a total of 89 PSMA-negative/FDG-positive targets identified. Median gross tumor volume (GTV) of 4.3 cm 3 , and median SUV max of 4.8 were found in 18 F-FDG PET/CT.…”
Section: Prospective or Retrospective Studies Using Psma-617 Or Psma-...mentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients presented extra decline in PSA (81%) and positive image-based response with 11/21 (52.3% presenting partial response [PR] or stable disease [SD]) with acceptable grade ≥3 toxicity in 15% of patients. 38 Gaudreault et al 39 evaluated 6 patients that were excluded from the LuPSMA trial with a total of 89 PSMA-negative/FDG-positive targets identified. Median gross tumor volume (GTV) of 4.3 cm 3 , and median SUV max of 4.8 were found in 18 F-FDG PET/CT.…”
Section: Prospective or Retrospective Studies Using Psma-617 Or Psma-...mentioning
confidence: 99%
“…Mader et al 38 demonstrated retrospectively in 26 mCRPC patients that an extension of treatment applying additional cycles after the usually recommended 6 cycles of PSMA-RLT could be a safe option in patients with a high volume of disease. Most patients presented extra decline in PSA (81%) and positive image-based response with 11/21 (52.3% presenting partial response [PR] or stable disease [SD]) with acceptable grade ≥3 toxicity in 15% of patients 38 …”
Section: Psma Radioligand Therapy In Prostate Cancermentioning
confidence: 99%
“…81% of patients had some further PSA response to treatment past six cycles with median PFS of 19 months (95% CI 15–23 months) and median OS of 29 months (95% CI 18–40). Only 15% of patients had ≥ Grade 3 hematologic toxicity [22]. In a separate prospective phase II analysis, thirty-five men with chemotherapy-naïve mCRPC were randomized to [ 177 Lu] lutetium-PSMA-617 versus docetaxel.…”
Section: Refining the Use Of Radiopharmaceuticals In Castration Resis...mentioning
confidence: 99%
“…6,13 On the basis of published RPT data showing that patients who received extended treatment courses exceeding these normal organ dose constraints still have limited toxicity, there is a specific concern in the field that the majority of patients treated with RPTs are undertreated. 4,[14][15][16][17][18][19][20][21][22] The inability to escalate beyond the above constraints in clinical trials leads to many phase I RPT trials stopping escalation before any DLT is observed, as opposed to other phase I trials with escalation guided primarily by clinical toxicity (Fig 1). This precludes treatment optimization with many RPT agents.…”
mentioning
confidence: 99%
“…In terms of the overall controversy noted above regarding AD constraints for bone marrow (2 Gy) and kidney (23 Gy), there is already evidence that these limits can often be safely exceeded in clinical practice in patients receiving multiple courses or extended cycles of RPT. 4,14,15,22 This suggests that current treatment regimens also merit reevaluation to assess whether larger initial administered activities per cycle are tolerable. In particular, in the bone marrow, acute toxicity is readily observable during the phase I DLT observation period (typically 3-8 weeks after administration).…”
mentioning
confidence: 99%